Desenvolvimento de aplicativo para monitoramento e comunicação de problemas de saneamento básico - Lima, Emerson Medeiros de (Universidade Federal Rural do Semi-Árido, 2019)
The present work focuses on the analysis of problems in urban sanitation, where there are several noises in the communication system. An Android application based on the Java programming language has been developed to simplify and automate the problem registration and reporting process, so that they are reported and resolved as quickly as possible. One of the differentials in the development of this application is the registration of the citizen in the system, which accounts for the amount of problems that it helped solve. Another highlight is the georeferencing of the site, providing, in addition to the address sent, additional information about the problem in question.
Artigo
Keywords: Aplicativo Android; Saneamento; Georreferenciamento; Problemas urbanos; Android app; Sanitation; Georeferencing; Urban problems; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA